Fluorescent Probes for Biomacromolecules Based on Monomethine Cyanine Dyes - Pavel G. Pronkin; Alexander S. Tatikolov (Chemosensors, 2023)
Monomethine cyanine dyes (MCDs) are widely applied as biomolecular probes and stains in biochemical and biomedical research. This is based on the ability of MCDs to associate with biomolecules (mostly nucleic acids) with significant fluorescent growth. The present review considers the works devoted to the properties of MCDs and the influence of noncovalent interactions with biomacromolecules on their properties, as well as their use as noncovalent probes and stains for various biomacromolecules. The synthesis and photonics (photophysics and photochemistry; in particular, the generation of the triplet state) of MCDs are also considered. Areas and prospects of the practical applications of MCDs in biochemistry and biomedicine are discussed.